Comparative study of hexavalent chromium removal by oxisol and synthesized iron minerals - Ramos, Raquel Lima; Faria, Danielle Bittencourt; Maronezi, Vanessa; de Campos, Valquiria [UNESP]; Furquim, Sheila Aparecida Correia; Shinzato, Mirian Chieko (Springer Nature, 2024)
The Cr(VI) removal efficiency of a Brazilian Oxisol collected from the A horizon (15.2% iron oxides, 4.6% organic matter, pH 4.3) was assessed and compared with synthesized iron minerals (SM), to mitigate contamination as a nature-based solution. Batch tests revealed that Cr(VI) removal efficiency was higher and faster for SM than for Oxisol: to remove ∼ 100% Cr(VI) from a solution containing 5 mg L− 1Cr(VI), SM took 24 h, while for the same concentration Oxisol removed 80% Cr(VI) in 30 days. At a higher concentration (30 mg L− 1), Cr(VI) removal efficiency dropped to 90% in 24 h for SM and 22% in 30 days for Oxisol. The Cr(VI) removal of Oxisol and SM fitted, respectively, to the pseudo-first and pseudo-second order, reflecting the way Cr(VI) is removed - by adsorption for SM (since pHPZC> pHsolution) and by reduction to Cr(III) for Oxisol organic matter. To simulate a contamination event, Oxisol was incubated with 300 mg L− 1 of Cr(VI) for 5, 10 and 30 days, followed by sequential extraction. The results of this test revealed that all the chromium was reduced to Cr(III) in all the time periods, and was mostly bound to the less mobile fractions of the soil: organic matter (75–85%), iron oxide/hydroxide (∼ 15%), and the residual fraction (< 5%); and only 5–10% was bound to the exchangeable fraction (more mobile). Although Cr(VI) is better adsorbed by SM, in Oxisol chromium is found in the less toxic form (trivalent) and bound to the less mobile fractions, promoting a more sustainable solution.
Keywords: Chromium; Nature-based solutions; Oxisol; Redox; Sequential extraction